ALTERNATIF INDIKATOR INFRASTRUKTUR DI KOTA SEMARANG: IDENTIFIKASI MENUJU PENGUKURAN BERBASIS KINERJA - Nediana Sarrasanti Ardinugroho; Wiwandari Handayani; Mada Sophianingrum (Jurnal Riptek, 2019)
Infrastructure is one critical aspect of city development. Based on the National Long-Term Development Plan (RPJPN) 2005-2025, enhance the capacity of infrastructure, and its system will impact the quality of the nation. The Sustainable Development Goals (SDGs) account for the development of resilient infrastructure in goal number nine. It is said that infrastructure not only increases the quality of life of the present generation but also has to accommodate the needs of the future generation. Semarang City, as one of the big cities in Indonesia, faces a problem of infrastructure as a result of its rapid development and population growth. The city has to provide quality infrastructure to its two million population as well as the suburbs around. Semarang City needs to address some urban problems like floods, congestion, adequate housing for the low-middle income people, and lack of green open space due to the inefficiency of the infrastructure system. As the infrastructure aspect is essential for the city, the government will need an instrument to measure infrastructure development performance. This study aims to analyse the alternatives for infrastructure development indicators in Semarang City. The method is descriptive and content analysis to review the current development plan of Semarang City, government regulations and infrastructure development literature. The result shows there are 204 indicators of infrastructure development of Semarang City, which grouped into seven aspects of infrastructures. The indicators then selected based on criteria to 148 indicators. The latter indicators then analysed based on its relevance with the Semarang City context and data availability that result in 67 final indicators that can be used to measure the performance of Semarang City infrastructure development.